2014
DOI: 10.1051/parasite/2014017
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection restrainsLitomosoides sigmodontisfilarial load and plasmodialP. yoeliibut notP. chabaudiparasitaemia in mice

Abstract: Infection with multiple parasite species is clearly the norm rather than the exception, in animals as well as in humans. Filarial nematodes and Plasmodium spp. are important parasites in human public health and they are often co-endemic. Interactions between these parasites are complex. The mechanisms underlying the modulation of both the course of malaria and the outcome of filarial infection are poorly understood. Despite increasing activity in recent years, studies comparing co- and mono-infections are very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Worms [Schistosoma sp (Hartgers & Yazdanbakhsh, 2006;Waknine-Grinberg et al, 2010;Bucher et al, 2011;Wang et al, 2013Wang et al, , 2014, Litomosoides sigmodontis (Karadjian et al, 2014), and Heligmosomoides polygyrus (Su et al, 2005)] and bacteria [Mycobacterium tuberculosis (Li & Zhou, 2013), Listeria monocytogenes (Qi et al, 2013), and Salmonella (Cunnington et al, 2012)] have been shown to alter the pathological outcome of malaria infection through bystander regulation of the host immunity. Specific to the PbA-ECM model, the mechanisms leading to ECM protection during co-infection were mostly due to the suppression of the pro-inflammatory response induced by the heterologous pathogen, which occurs from 4 days post-Plasmodium infection onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Worms [Schistosoma sp (Hartgers & Yazdanbakhsh, 2006;Waknine-Grinberg et al, 2010;Bucher et al, 2011;Wang et al, 2013Wang et al, , 2014, Litomosoides sigmodontis (Karadjian et al, 2014), and Heligmosomoides polygyrus (Su et al, 2005)] and bacteria [Mycobacterium tuberculosis (Li & Zhou, 2013), Listeria monocytogenes (Qi et al, 2013), and Salmonella (Cunnington et al, 2012)] have been shown to alter the pathological outcome of malaria infection through bystander regulation of the host immunity. Specific to the PbA-ECM model, the mechanisms leading to ECM protection during co-infection were mostly due to the suppression of the pro-inflammatory response induced by the heterologous pathogen, which occurs from 4 days post-Plasmodium infection onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent observation of granulomas, mainly constituted of T cells and macrophages, in the lung of L . sigmodontis infected mice at day 8 post inoculation also reinforce this hypothesis [13]. However, the presence of an inflammatory reaction in the pulmonary tissue has not yet been addressed.…”
Section: Introductionmentioning
confidence: 89%
“…These forms of immunomodulation by helminths effect bystander immune responses and can improve autoimmune diseases [ 5 8 ] or allergy [ 9 12 ] while efficacy of vaccinations is reduced [ 13 , 14 ]. Furthermore, several epidemiological reports and animal studies have demonstrated that helminth infections alter immune responses to unrelated pathogens [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%